The conflict of the faculties : perspectives on artistic research and academia. - Borgdorff, Henk (Leiden : Leiden university press, 2012)
The thesis is about artistic research - what it is, or what it could be. And it is about the place that artistic research could have in academia, within the whole of academic research. It is also about the ways we speak about such issues, and about how the things we say (in this study and elsewhere) cause the practices involved to manifest themselves in specific ways, while also setting them into motion. In this sense, the thesis not only explores the phenomenon of artistic research in relation to academia, but it also engages with that relationship. This performative dimension of the thesis is interwoven with its constative and interpretive dimensions. If the thesis succeeds in its aims, it will not only advance knowledge and understanding of artistic research, but it will further the development of this emerging field.
Ook verschenen als proefschrift Universiteit Leiden.
boek